2017
DOI: 10.1017/jfm.2017.635
|View full text |Cite
|
Sign up to set email alerts
|

Spectral energy cascade in thermoacoustic shock waves

Abstract: We have investigated thermoacoustically amplified quasi-planar nonlinear waves driven to the limit of shock-wave formation in a variable-area looped resonator geometrically optimized to maximize the growth rate of the quasi-travelling-wave second harmonic. Optimal conditions result in velocity leading pressure by approximately 40• in the thermoacoustic core and not in pure travelling-wave phasing. High-order unstructured fully compressible Navier-Stokes simulations reveal three regimes: (i) Modal growth, gover… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 47 publications
2
32
0
Order By: Relevance
“…However, on the contrary, the growth rate is greater than the linear one. Recently Gupta et al 15) examined the step-up behavior in the experiment by Yazaki et al 4) in detail by the computational fluid dynamics. From their results, the range between 10 À3 and 10 À2 belongs to their second regime of hierarchial spectral broadening subsequent to the first regime of the modal growth predicted by the linear theory.…”
Section: Marginal Conditions For the Onset Of Instabilitymentioning
confidence: 99%
“…However, on the contrary, the growth rate is greater than the linear one. Recently Gupta et al 15) examined the step-up behavior in the experiment by Yazaki et al 4) in detail by the computational fluid dynamics. From their results, the range between 10 À3 and 10 À2 belongs to their second regime of hierarchial spectral broadening subsequent to the first regime of the modal growth predicted by the linear theory.…”
Section: Marginal Conditions For the Onset Of Instabilitymentioning
confidence: 99%
“…In previous numerical investigations [9] -inspired by the experimental setups in [16,17] -the present authors have demonstrated the existence of an equilibrium spectral energy cascade in quasi-planar weak shock waves sustained by thermoacoustic instabilities in a resonator. The latter inject energy only at scales comparable to the resonator length (large scales); harmonic generation then takes place, leading to spectral broadening and progressive generation of smaller scales until viscous losses, occurring at the shock-thickness scale, dominate the energy cascade.…”
Section: Introductionmentioning
confidence: 80%
“…Nonlinear wave processes are observed in a variety of engineering and physics applications such as acoustics [1,2], combustion noise [3,4], jet noise [5][6][7], thermoacoustics [8,9], surface waves [10], and plasmaphysics [11], requiring nonlinear evolution equations to describe the dynamics of perturbations. In the case of high amplitude planar acoustic wave propagation, two main nonlinear effects are present: acoustic streaming [2,12] and wave steepening [1,13].…”
Section: Introductionmentioning
confidence: 99%
“…2βẼ quantifies the rate of energy accumulation, dĨ/dx is the work source defined in the previous section,R is an energy redistribution term.P andD are the thermoacoustic production and dissipation, respectively. The energy redistribution term in the acoustic energy budgets of solid thermoacoustics cannot be found in the fluid counterpart of the same equations [19]. This term is absent in fluids because it is canceled in the algebraic derivations by expressing the variation of mean density according to the ideal gas law, as a function of the mean temperature gradient.…”
Section: Acoustic Energy Budgetsmentioning
confidence: 99%